Steam Flow Rate Determination for Critical Flow Condition using Numerical Analysis - Febrynzki, Davy
A series of tests are carried out on the geothermal wells to obtain accurate information about the condition of a reservoir. One of the types of well testing is called discharge test pressure lip method, the test utilized the critical flow phenomena to determine the value of mass rate when the fluid flows out from the reservoir. There are three researchers who conducted a study on the phenomenon of critical flow using the lip pressure method. Among the researchers are Chien-Schrodt, James, and Hiriart. Each of these researchers used different empirical equations to determine the rate of mass from a critical flow. James and Hiriart respectively formulated their equations based on experimental and analytical results, but in Chien-Schrodt research they use equation offered by King-Crocker in determining the mass flow rate in critical flow condition. In this study, the values of the mass rate from the result of each equation are compared in the same experimental conditions held by Chien-Schrodt and James. Such conditions are the fluid state phase which is saturated vapor and two-phase, and the condition of critical pressure varies from 2 bar to 22 bar. While using a 0,375-in to 10-in of critical diameter with neck length from 6-in up to 12-ft. The flow simulations are performed with software called ANSYS FLUENT 13.0™ using the same condition when Chien-Schrodt and James performed their experiments. The simulation results showed a difference in the value of the mass flow rate from the results of James Formula, Hiriart Formula, and King-Crocker Formula at different pressure and steam quality. Therefore, Equation 4.14 and 4.15 can be formulated based on the simulation results in critical flow for two phase and saturated vapor condition.